Investigation on the Fracturing Permeability Characteristics of Cracked Specimens and the Formation Mechanism of Inrush Channel from Floor - Jianning Wang; Weitao Liu; Jianjun Shen (Shock and Vibration)
To study the fracture characteristics and the permeability change law of the cracked specimens during the complete stress-strain process, a mechanical model was constructed, from which different types of crack initiation angles were obtained. The crack inclination angles under uniaxial compression, confining compression, and confining tension, and the influence of confining pressure and pore water pressure on the crack propagation and permeability of rock mass were investigated and simulated with RFPA-Flow software using prefabricated crack models with crack initiation angles of 30°, 45°, and 60°. Furthermore, the formation mechanism of inrush channel from floor was qualitatively analyzed. The results indicated that the theoretical initiation angles of wing cracks, secondary coplanar cracks, and secondary inclined antiwing cracks were found to be 70.53°, 0°, and 123.8°, which were consistent with the simulation results. The crack propagation was mainly concentrated at the postpeak stage of the complete stress-strain curve, causing the peak of seepage velocity to lag behind the stress peak. For the case with a constant confining pressure, the rate of crack initiation and propagation to final failure was positively correlated with the internal pore pressure. For the case with a constant water pressure, the speed of crack initiation and propagation to final failure decreased first and then increased as the confining pressure increased. In addition, the longitudinal propagation of wing cracks and the increase in permeability were prone to occur in the low confining pressure zone, which induced the formation of water inrush channels. The research result provides an improved understanding for predicting and preventing water inrush disasters.